Upaya Meningkatkan Hasil Belajar Siswa Kelas V SD Negeri 024 Rambah Tentang Materi Kenampakan Alam Pada Mata Pelajaran IPS Dengan Menggunakan Metode Kelompok Tahun Pelajaran 2016/2017 - Asmaniar Asmaniar (Indonesian Journal of Basic Education, 2018)
The subject of IPS is one of the areas of curricular study at elementary school level (SD). Due to the low understanding of students on this lesson, especially the subject of economic activity in utilizing natural resources in class V SD Negeri 024 Rambah, the authors make improvements in learning. Improvement of learning is done through Classroom Action Research (PTK) with three learning cycles. The research activities were carried out at SD Negeri 024 Rambah in the 2016/2017 school year on V-student of 20 students, consisting of 7 men and 13 women. This study aims to improve student learning outcomes and activities in the subjects of social studies IPS material in the utilization of natural resources using group work methods. After teaching and learning activities using group work methods, student learning outcomes and activities have increased. This is shown from the data collected, in the pre-cycle learning activities only 7 students who get the value of ≥ KKM with a grade point average of 41.5. Student learning outcomes continue to increase in cycle I, and in cycle III only 2 students who have not reached the value of KKM with an average grade of 80.5. The percentage of student completeness increased, from 35% in pre-cycle learning activities to 90% in the improvement of learning cycle II. So the description of the data collected can be concluded that the use of group work methods can improve student learning outcomes and activities on the subjects of social studies on economic activities in the utilization of natural resources in class V SD Negeri 024 Rambah. Thus, the method of group work is one of the effective learning methods in improving student learning outcomes and activities on the subjects of social studies IPS material in the utilization of natural resources